Alternative measure of financial development and investment-cash flow sensitivity: Evidence from an emerging economy - Gaurav Gupta; Jitendra Mahakud (Financial Innovation, 2019)
This study examines the impact of financial development on corporate investment in terms of their influence on financing constraints. This study also tries to find the effect of financial development on the investment-cash flow sensitivity across the size, degree of financial constraints and group affiliation of the firm. This study employs dynamic panel data model or more specifically system generalized method of moments (GMM) estimation technique. The estimation results reveal that cash flow affects the investment decision of the company positively, which implies that Indian firms are financially constrained. Also, we observe that financial development reduces the investment-cash flow sensitivity and the effect of financial development is more prominent for small size and standalone firms. The results are robust across the period and, for both financially constrained and unconstrained firms. This study contributes to the existing literature by analyzing the impact of financial development on the role of cash flow in determining investments undertaken by the Indian firms, which is an unexplored issue from an emerging market perspective.
Keywords: 650; Business groups; Cash flow; Corporate investment; Financial constraints; Financial development; Firm size; Generalized method of moments